2014
DOI: 10.1088/0031-9155/60/1/233
|View full text |Cite
|
Sign up to set email alerts
|

Real-time prediction and gating of respiratory motion using an extended Kalman filter and Gaussian process regression

Abstract: Motion-adaptive radiotherapy aims to deliver a conformal dose to the target tumour with minimal normal tissue exposure by compensating for tumour motion in real time. The prediction as well as the gating of respiratory motion have received much attention over the last two decades for reducing the targeting error of the treatment beam due to respiratory motion. In this article, we present a real-time algorithm for predicting and gating respiratory motion that utilizes a model-based and a model-free Bayesian fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…This technology has been critical to aerospace engineering, including guiding Apollo missions to the moon 1 . More recently, it has been used to forecast the development or worsening of chronic diseases 4,812 , and we have used it to forecast OAG progression 13 .…”
Section: Methodsmentioning
confidence: 99%
“…This technology has been critical to aerospace engineering, including guiding Apollo missions to the moon 1 . More recently, it has been used to forecast the development or worsening of chronic diseases 4,812 , and we have used it to forecast OAG progression 13 .…”
Section: Methodsmentioning
confidence: 99%
“…Machine learning techniques are particularly well suited to this application due to the similarity of future breath characteristics with previously recorded breaths. A large body of work has shown neural network, SVM, manifold learning and kernel density estimation can efficiently predict respiratory motion based on previously measured motion traces [153][154][155][156][157][158][159]. Other applications of machine learning involve prediction of motion extent based on tumour size and location in the lungs, automatic diaphragm motion trajectory assessment and incorporation of lung tumour motion into patient setup and prediction of tumour baseline shifts in the short term (approximately 5 s) [160][161][162][163].…”
Section: Image Guidance and Motion Managementmentioning
confidence: 99%
“…Several studies have used ML algorithms for predicting tumour motion based on past motion, 72–89 including in MRI‐guided radiotherapy 90–92 and ultrasound‐guided radiotherapy 93 . A comparison study of ML algorithms was made by Sharp et al.…”
Section: Prediction Of Tumour Motionmentioning
confidence: 99%
“…Several studies have used ML algorithms for predicting tumour motion based on past motion, [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] including in MRI-guided radiotherapy [90][91][92] and ultrasound-guided radiotherapy. 93 A comparison study of ML algorithms was made by Sharp et al and showed that most ML algorithms have a lower localisation error compared to no prediction.…”
Section: Prediction Of Tumour Motionmentioning
confidence: 99%